V2 vasopressin receptor mutations: future personalized therapy based on individual molecular biology - Erdélyi, László Sándor; Hunyady, László; Balla, András (Frontiers in Endocrinology, 2023)
The diluting and concentrating function of the kidney plays a crucial role in regulating the water homeostasis of the body. This function is regulated by the antidiuretic hormone, arginine vasopressin through the type 2 vasopressin receptor (V2R), allowing the body to adapt to periods of water load or water restriction. Loss-of-function mutations of the V2R cause X-linked nephrogenic diabetes insipidus (XNDI), which is characterized by polyuria, polydipsia, and hyposthenuria. Gain-of-function mutations of the V2R lead to nephrogenic syndrome of inappropriate antidiuresis disease (NSIAD), which results in hyponatremia. Various mechanisms may be responsible for the impaired receptor functions, and this review provides an overview of recent findings about the potential therapeutic interventions in the light of the current experimental data.